A novel method of the Rough Interval-valued Intuitionistic Fuzzy Sets - Xia Li; Zhan-Ao Xue; Li-Ping Wei; Feng Cen (2009 International Conference on Machine Learning and Cybernetics, 2009)
In this paper, by combining the rough sets theory and intuitionistic fuzzy special sets theory, the model of the rough interval-valued intuitionistic fuzzy sets is defined, some basic operations of the model are given, and the properties of the model are discussed. The discussion is the emphasis in the properties of complement. By discussing, co-normality, normality, duality are established in rough interval-valued intuitionistic fuzzy sets, multiplication and addition are not.